Opportunities to Use the Clean Development Mechanism (CDM) and Other Options to Face the Climate Change. An Application to Peru - Quiroz Melgar, Carlos Javier (2012)
Descargue el texto completo en el repositorio institucional del KTH Royal Institute of Technology: https://hdl.handle.net/20.500.12380/167082